Efeitos do destreino de um programa de exercícios multicomponentes na função física de pessoas idosas da comunidade: comparação entre o destreino de férias de verão vs destreino causado pela pandemia de COVID-19 - Casoni, Fernanda Omizollo (Universidade Federal de São Carlos, 2024)
To compare the effects of detraining from a multicomponent exercise program caused by the COVID-19 pandemic with detraining due to a summer vacation period on the physical function of community-dwelling older adults. Methods: This is an observational, longitudinal, and retrospective study. The study included older adults (≥ 60 years) who were participants in the university extension project "Geriatric Revitalization" and were engaged in a multicomponent exercise program interrupted by the COVID-19 pandemic. The participants were assessed in November 2019 (T1) and March 2020 (T2), before the pandemic, and in September 2021 (T3), 18 months after the pandemic began. Physical function was evaluated using the handgrip strength test, 30-second chair stand test, 30-second single-leg stance test, and Timed Up and Go (TUG) test. To assess detraining caused by the COVID-19 pandemic, summer vacation detraining, and to compare the two, a repeated measures ANOVA with Tukey's post hoc test was conducted. The analyses were performed using JAMOVI Software (version 2.3.18), with statistical significance set at p < 0.05. Results: Sixty-seven older adults were assessed at T1, and after the summer vacation at T2, only 28 underwent evaluation. Following the suspension of the exercise program in March 2020 due to the COVID-19 pandemic, only 32 older adults were evaluated at T3. At baseline, the participants had a mean age of 72 ± 7,08 years, and 89,3% were female. There were no significant differences in detraining caused by the summer vacation (p > 0.05). However, when compared to detraining caused by the COVID-19 pandemic, there was a reduction in lower limb strength (Mean difference = -1.54; p < 0.001; d = 0.87) and a decline in functional mobility, reflected in an increased time to complete the TUG test (Mean difference = 1.55; p < 0.001; d = 2.94). Conclusion: Only the detraining caused by the COVID-19 pandemic significantly impacted the physical function of older adults participating in a multicomponent exercise program, leading to a reduction in lower limb strength and functional mobility.
Effects of detraining from a multicomponent exercise program on the physical function of older adults: comparison between summer vacation detraining vs detraining caused by the COVID-19 pandemic
Keywords: Pessoa idosa; Exercício Físico; Destreino; Função física; COVID-19; Interrupção do Tratamento; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL